Planning for the integration of refugee and host communities in Turkana County, Kenya - Yuka Terada; David Evans; Dennis Mwaniki (Forced Migration Review, 2017)
The Kalobeyei New Settlement focuses on the creation of a spatial plan to guide settlement in both the short and the long term to the benefit of both host community and refugees.